(untitled) (Applied Biological Research, 2019)
Forty four genotypes of paprika (Capsicum annuum L.) were evaluated at Horticultural Research Station, Lam farm, Guntur (India) in the year 2017 to assess variability, character association and path analysis among the yield and yield attributing characters. High magnitudeof PCV and GCV were observed for characters viz., number of fruits plant-1, fruit diameter and dry fruit yield plant-1. Predominance of additive gene action was observed for days to maturity, number of fruits plant-1, fruit length, fruit diameter, number of seeds fruit-1 and dry fruit yield plant-1 which may be exploited through simple selection. Dry fruit yield plant-1 showed positive significant correlation with the number of fruits plant-1. The path analysis revealed that the number of fruits plant-1, fruit length and fruit diameter had positive direct effect on yield plant-1 indicating that direct selection based on these traits may be helpful in evolving high yielding varieties of paprika.